Police satisfaction and disorder: results from a survey of a semi-rural community - Lytle, Daniel J. (Policing and society, 2017)
This paper explores the relationship between disorder and police satisfaction while controlling for other relevant factors related to police satisfaction such as race, gender, age, and prior police contact. We present results from a survey of residents in a semi-rural southern city. This survey location provides a unique opportunity to explore the effects of disorder and social cohesion on police satisfaction in an environment that incorporates elements of both urban and rural environments. The results indicate that white respondents, older respondents, and those that were more integrated into their neighbourhoods were more satisfied with the police. Variation in the levels of disorder did not, however, have an impact of citizen satisfaction. The implications for these findings are also discussed.